Perbedaan Hasil Belajar Matematika Siswa MI dengan Menggunakan Animasi Avatar Zepeto dan Powerpoint - Arsella, Osta; Sari, Rita; Anggreni, Fenny (the Faculty of Education and Teacher Training of the Institut Agama Islam Negeri (IAIN) Langsa, 2022)
Learning outcomes are the results that a person gets after going through the learning process. From the results of observations that have been made by researchers on students of grade IV MIN 4 Aceh Tamiang, there are student learning outcomes that are still relatively low because the media used by teachers is not varied. One innovative medium to apply is to use zepeto avatar animations and powerpoints. The purpose of this study was to see the differences in the learning outcomes of students who used zepeto avatar animations with students who used powerpoints in mathematics subjects in class IV MIN 4 Aceh Tamiang. The research uses a quantitative approach with the type of quasy experiment or pseudo-experiment with a posttest-only control group design. The research sample amounted to 35 students selected in two classes, namely the IVA class of 18 students and the IVB class of 17 students. The results of the hypothesis test using the independent sample t-test obtained the Sig value. 0.021<0.05.